Interfigural readings of the Gospel of John - Kitzberger, Ingrid Rosa (Early Christianity and its literature ;, 2019)
"This volume of collected essays introduces the concept of interfigurality, the interrelationship between Johannine characters where they intersect the Synoptic Gospels and the Hebrew Bible. The essays are informed by a narrative-critical reader response, (post)feminist hermeneutics, and an autobiographical approach to biblical texts. This volume encourages transformative encounters between present readers and the ancient biblical texts"--